2016
DOI: 10.1177/1535370216650940
|View full text |Cite
|
Sign up to set email alerts
|

Induction of matrix metalloproteinase-1 by tumor necrosis factor-α is mediated by interleukin-6 in cultured fibroblasts of keratoconus

Abstract: Inflammatory molecules and matrix metalloproteinase (MMPs) have been found over-expressed in the tear film of patients with keratoconus. However, the mechanistic link between inflammatory molecules and MMPs in the pathogenesis of keratoconus remains still elusive. Therefore, we investigated the effect of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) on MMP-1 expression and used IL-6 antibody (IL-6 Ab) to examine the role of IL-6 on TNF-α mediated regulation of MMP-1 in fibroblasts of normal cornea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…The analysis revealed strong functional interaction between members of the MMP family (MMP1, 2, 3) and IL-6 (Fig. S3 ), conforming and extending studies demonstrating that IL-6 regulates tissue MMPs 35 , 36 .
Figure 2 OCT regulates proteins involved in wound healing and immune response.
…”
Section: Resultssupporting
confidence: 83%
“…The analysis revealed strong functional interaction between members of the MMP family (MMP1, 2, 3) and IL-6 (Fig. S3 ), conforming and extending studies demonstrating that IL-6 regulates tissue MMPs 35 , 36 .
Figure 2 OCT regulates proteins involved in wound healing and immune response.
…”
Section: Resultssupporting
confidence: 83%
“…MMP-1 mRNA and protein expression in these cells 80 . MMP-9 mRNA, protein and overall activity levels in corneal epithelial cells in-vitro is stimulated by treatment with TGF-β, IL-1β and TNF-α 36,40,81 , and induction of both MMP-9 and MMP-1 mRNAs can be initiated by platelet-activating factor (PAF), an important inflammatory mediator which accumulates in the cornea following an injury 82 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…According to recent studies, a few types of matrix metalloproteinase (MMP) play vital roles in the development of inflammation in intestinal epithelial cells. Multiple studies have reported that IL-1β and TNFα increase expression of MMP [ 39 , 40 ]. At the same time, MMPs play a role in promoting ECM degradation following UVB damage in skin dermis and epidermal cells.…”
Section: Discussionmentioning
confidence: 99%